Effects of 8-Weeks Concurrent Strength and Aerobic Training on Body Composition, Physiological and Cognitive Performance in Older Adult Women. - Morente-Oria, Honorato Fernando; Ruiz-Montero, Pedro Jesus; Chiva-Bartoll, Óscar; González-Fernández, Francisco Tomás (MDPI, 2020)
Despite plenty of evidence supporting the advantages of regular physical exercise amongst older women, it is not clear what the best methodology is to improve these parameters. Considering the growth of older population and aging process, this study analyses an 8-weeks concurrent training intervention; (2) Methods: A total of 48 older women participated in concurrent strength and aerobic exercises training intervention being used to know physical and cognitive improvements in older women through physical, physiological and vigilance tests; (3) Results: Significant differences were found in weight and body mass index (BMI) between pre-intervention and post-intervention and even better results, but non-significative, in maximum oxygen consumption (VO2max), total fat percentage and skeletal muscle mass. Additionally, we found cognitive improvements in vigilance (RT) related to executive functions. (4) Conclusions: An 8-weeks concurrent training program (strength and aerobic exercises) give another efficient possibility to obtain better physical, physiological and cognitive improvements in older women.
Keywords: Ejercicio físico - Aspectos fisiológicos; Mujeres; Cuerpo humano - Composición; Older adults; Concurrent training; Cognitive performance